Effects of abomasally infused amylase and increasing amounts of corn starch on fecal excretion of starch, total and microbial nitrogen, and volatile fatty acids in heifers1. (20th July 2019) - Robbers, Kristina; Westreicher-Kristen, Edwin; Troescher, Arnulf; Susenbeth, Andreas
Abstract: The aim of the present study was to study the effect of exogenous amylase on postruminal disappearance of increasing amounts of corn starch being infused into the abomasum of heifers, and to detect a possible limitation of starch digestion in the small intestine. Four rumen-fistulated heifers (2 German Black Pied and 2 Jersey × German Black Pied) with an initial BW of 565 ± 6 kg were fed 5.6 kg DM/d of a diet targeted to contain only a negligible amount of starch. Animals were assigned randomly to a crossover trial with 2 experimental periods lasting 35 d each with 10 d of diet adaption followed by 25 d of sample collection. During the sampling period, each animal was abomasally infused with native corn starch at 5 levels (953, 1, 213, 1, 425, 1, 733, and 1, 993 g DM/d) each for a 5-d period with and without exogenous amylase, respectively. At days 6 to 10 the heifers received an abomasal infusion of starch in amounts of 724 g/d. Feces were sampled 4 times a day during the collection periods. Titanium dioxide was ruminally administered (10 g/d) to estimate fecal excretion. Purine bases in feces were determined and used as a marker for microbial N excretion. Fecal excretion of microbial N increased linearly with increasing level of starch infusion ( P < 0.001), indicating a constant proportion of the infused starch being fermented in the hindgut. In contrast, the apparent digestibility of starch from the total postruminal tract decreased linearly from 90% to 80% ( P < 0.001) when the intestinal starch supply increased from 1 to 2 kg/d. There is strong evidence based on the increasing starch excretion with feces and the indication of a constant proportion of infused starch being fermented in the hindgut for a decreasing efficiency of starch digestion in the small intestine with increasing intestinal supply. Amylase administration increased fecal excretion of butyrate ( P = 0.04) and tended to increase isovalerate excretion ( P = 0.06). However, amylase did not affect fecal excretion of microbial N or starch, suggesting that pancreatic amylase activity may not be the primarily limiting factor of postruminal starch digestion in heifers when corn starch is abomasally infused in amounts up to 2 kg/d.